Comparative analysis of effectiveness of asthma control test-guided treatment versus usual care in patients with asthma from China. (June 2021) - Ye, Ling; Gao, Xiwen; Tu, Chunlin; Du, Chunling; Gu, Wenchao; Hang, Jingqing; Zhao, Lei; Jie, Zhijun; Li, Hailing; Lu, Yueming; Wang, Jin; Jin, Xiaoyan; et al.
Abstract: Objective: The present study compared the effectiveness of asthma control test (ACT)-guided treatment vs. usual care (UC) in patients with asthma from China. Methods: This prospective, phase IV, multicenter, cluster-randomized, open-label 24-week study was conducted in China; patients were randomized to either ACT-guided treatment or UC group. The patients recorded peak expiratory flow, symptoms, and medication in a diary card every day and completed ACT at every clinic visit. For the UC group, patients completed ACT after the physician's treatment decision. Results: In total, 83.6% patients (n = 443/530; ACT: n = 209, UC: n = 234) completed the study. A significantly higher proportion of patients (adjusted OR [95% CI]: 7.87 (1.29, 48.11; p = 0.027) responded to the treatment and had ACT total score ≥20 or demonstrated an improvement of >3 points in ACT total score in ≥1 post-baseline assessment in the ACT-guided treatment vs. UC group. A higher proportion of patients had an ACT total score ≥20 and an improvement of >3 points in ACT total score at Week 24 in the ACT-guided treatment vs. the UC group (adjusted OR (95% CI):2.28 (1.07, 4.85; p = 0.036). A significant difference (p = 0.005) in change from baseline in ACT total score was observed in ACT-guided treatment vs. UC group at Week 24. The mean annual exacerbation rate was similar in both the groups. Conclusions: ACT-guided treatment was more effective in achieving ACT total score ≥20 or showing an improvement of >3 points in the ACT total score and well tolerated compared with UC treatment in the 24-week treatment period. Trial registration: Clinical trials.gov Identifier: NCT02868281, https://clinicaltrials.gov/ ; GlaxoSmithKline study ID: 201097, https://www.gsk-studyregister.com/ . Highlights: More patients had improved ACT total score in ACT-guided vs. UC treatment group. FEV1 and ACT scores were higher in ACT-guided vs. UC treatment group. The mean annual exacerbation rate was similar in both the groups. Overall, ACT-guided was more effective than UC treatment in this 24-week study.